Neutralizing Antibodies Against Factor VIII Can Occur Through a Non-Germinal Center Pathway - Patel, Seema R.; Lundgren, Taran S.; Baldwin, Wallace Hunter; Cox, Courtney; Parker, Ernest T.; Healey, John F.; Jajosky, Ryan P.; Zerra, Patricia E.; Josephson, Cassandra D.; Doering, Christopher B.; Stowell, Sean R.; Meeks, Shannon L. (Frontiers in Immunology, 2022)
Humoral immunity to factor VIII (FVIII) represents a significant challenge for the treatment of patients with hemophilia A. Current paradigms indicate that neutralizing antibodies against FVIII (inhibitors) occur through a classical CD4 T cell, germinal center dependent process. However, clinical observations suggest that the nature of the immune response to FVIII may differ between patients. While some patients produce persistent low or high inhibitor titers, others generate a transient response. Moreover, FVIII reactive memory B cells are only detectable in some patients with sustained inhibitor titers. The determinants regulating the type of immune response a patient develops, let alone how the immune response differs in these patients remains incompletely understood. One hypothesis is that polymorphisms within immunoregulatory genes alter the underlying immune response to FVIII, and thereby the inhibitor response. Consistent with this, studies report that inhibitor titers to FVIII differ in animals with the same F8 pathogenic variant but completely distinct backgrounds; though, how these genetic disparities affect the immune response to FVIII remains to be investigated. Given this, we sought to mechanistically dissect how genetics impact the underlying immune response to FVIII. In particular, as the risk of producing inhibitors is weakly associated with differences in HLA, we hypothesized that genetic factors other than HLA influence the immune response to FVIII and downstream inhibitor formation. Our data demonstrate that FVIII deficient mice encoding the same MHC and F8 variant produce disparate inhibitor titers, and that the type of inhibitor response formed associates with the ability to generate germinal centers. Interestingly, the formation of antibodies through a GC or non-GC pathway does not appear to be due to differences in CD4 T cell immunity, as the CD4 T cell response to an immunodominant epitope in FVIII was similar in these mice. These results indicate that genetics can impact the process by which inhibitors develop and may in part explain the apparent propensity of patients to form distinct inhibitor responses. Moreover, these data highlight an underappreciated immunological pathway of humoral immunity to FVIII and lay the groundwork for identification of biomarkers for the development of approaches to tolerize against FVIII.